Crystal Structure of an Aminoglycoside 6'-N-Acetyltransferase - Wybenga-Groot, Leanne (My University, 1999)
The overwhelming increase in antibiotic resistant bacterial strains poses a serious public health problem, with multiply-resistant strains becoming an important cause of mortality in hospitals. The predominant mechanism of resistance to aminoglycoside antibiotics involves enzymatic modification of the drug, rendering it ineffective. The crystal structure of the aminoglycoside-modifying enzyme aminoglycoside acetyltransferase(6')-Ii (AAC(6')-Ii) in complex with its cofactor, acetyl coenzyme A (AcCoA), was determined at 2.7 Å resolution by the multiwavelength anomalous diffraction technique. The resolution of this structure was subsequently extended to 2.15 Å by molecular replacement, with no significant changes in the topology of the complex. The enzyme was found to exhibit a novel CoA-binding fold, with the cofactor bound in a cleft between the N-and C-terminal arms of the protein molecule. Although the enzyme packs as a monomer in the I4₁32 crystal form, the most probable physiological dimer of the complex was determined through analysis of a number of symmetry-related molecules. The crystal structure of the AAC(6')-Ii•AcCoA complex was compared to the structures of three members of a large superfamily of GCN5-related 𝘕-acetyltransferases (GNATs), namely yeast histone acetyltransferase HAT1, 𝘕-myristoyltransferase, and aminoglycoside acetyltransferase(3)-Ia. Despite negligible sequence similarity between these GNAT superfamily members, a distinct folding pattern is conserved in all four structures. This establishes AAC(6')-Ii as a structural homolog of enzymes with protein acetylating activity, supporting the hypothesis that the enzyme may possess another physiological function in 𝘌𝘯𝘵𝘦𝘳𝘰𝘤𝘰𝘤𝘤𝘶𝘴 𝘧𝘢𝘦𝘤𝘪𝘶𝘮.
Crystal Structure of AAC(6')-Ii
Keywords: crystal; aminoglycoside; acetyltransferase; acetyl